Load capacity coefficient evaluation of three-layered journal bearing with slip - Rao, T.V.V.L.N. (Penerbit UTM Press, 2016)
Analysis of three-layered journal bearing with slip on bearing surface is presented. A modified classical Reynolds equation is derived for slip on bearing surface taking into consideration of bearing surface, core and journal surface layers. The modified Reynolds equation is derived taking into consideration of lubricant layerâs film thickness, viscosities and slip on the bearing surface. Navier slip boundary conditions are used to analyze slip. Results of load capacity coefficient are presented for three-layered and two-layered journal bearing with slip. The load capacity coefficient decreases with bearing surface with slip. For a three-layered journal bearing with slip, high viscosity bearing surface layer results in higher load capacity coefficient. Â© 2016 Penerbit UTM Press. All rights reserved.